Introduction to matrices and vectors - Schwartz, Jacob T. (New York : McGraw Hill Education, 1961)
The theory of matrices occupies a strategic position both in pure and in applied mathematics. The most famous application is doubtless the application to atomic physics; the prevalence of such terms as matrix mechanics, scattering matrix, spin matrices, annihilation and creation matrices gives vivid testimony to the decisive importance of matrix theory for the modern physicist. In economics we have the input-output matrix, computed at great expense by the Bureau of Labor Statistics, as well as the game- theoretical payoff matrix. In statistics we have transition matrices, as well as many other sorts of matrices; in engineering, the stress matrix, the strain matrix, and many other important matrices.
Chapter 1. Definition, equality and addition of matrices -- Chapter 2. Multiplication of matrices -- Chapter 3. Division of matrices -- Chapter 4. Vectors and linear equations -- Chapter 5. Special matrices of particular interest -- Chapter 6. More algebra of matrices and vectors -- Chapter 7. Eigenvalues and eigenvectors -- Chapter 8. Infinite series of matrices.
Includes index.
Keywords: MATRICES